Impact of fertilizings on accumulation of carbohydrates in blueberry fruits on recultivated cutover peatlands in the north of Belarus - Rupasova, Zhanna A.; Yakovlev, Alexander P.; Krinitskaya, Natalia B.; Yaroshuk, Andrey A.; Savosko, Irina V.; Goncharova, Liudmila V.; Aleschenkova, Zinaida M.; Kolomiets, Emilia I. (Journal of the Belarusian State University. Ecology, 2019)
The paper deals with the results of a comparative study of morphometric, bioproduction and biochemical characteristics of Vaccinium angustifolium fruits and the intraspecific hybrids of Northcountry and Northblue (grown in the experimental culture at the recultivated opencast peatland in the north of the Republic) against the background of full mineral (N16Р16К16) and microbial (liquid preparation «MaKlor» in concentrations of 10 and 50 %; liquid and dry forms of «Agromik» preparation; liquid preparation «Bactopin») fertilizers application under differentiated and joint application. Found that the enhancement of the mineral nutrition of examined blueberry taxa did not have a significant effect on the size of the fruits, but contributed to an increase in their yield by 17–26 %, compared with the control. The most significant differences revealed against the background of N16P16K16 with 50 % fertilizer «MaKlor» (V. angustifolium and Northcountry variety), as well as «Agromik» preparation (Northblue variety). The least increase in yield took place against the background of the application of «Bactopin». The use of both microbial and mineral fertilizers contributed to the enrichment of blueberry fruits with dry substances (by 5–21 % compared to the control), with a pronounced depletion of free organic and ascorbic acids by 4–50 % and 7–29 %, respectively, with the most significant manifestation of the response in a narrow-leafed species.
Keywords: opencast peatland; recultivation; mineral fertilizers; microbial preparations; effectiveness; blueberries fruits; biochemical composition